Unraveling the mechanism of furfural tolerance in engineered Pseudomonas putida by genomics - Zou, Lihua; Jin, Xinzhu; Tao, Yuanming; Zheng, Zhaojuan; Ouyang, Jia (Frontiers in Microbiology, 2022)
As a dehydration product of pentoses in hemicellulose sugar streams derived from lignocellulosic biomass, furfural is a prevalent inhibitor in the efficient microbial conversion process. To solve this obstacle, exploiting a biorefinery strain with remarkable furfural tolerance capability is essential. Pseudomonas putida KT2440 (P. putida) has served as a valuable bacterial chassis for biomass biorefinery. Here, a high-concentration furfural-tolerant P. putida strain was developed via adaptive laboratory evolution (ALE). The ALE resulted in a previously engineered P. putida strain with substantially increased furfural tolerance as compared to wild-type. Whole-genome sequencing of the adapted strains and reverse engineering validation of key targets revealed for the first time that several genes and their mutations, especially for PP_RS19785 and PP_RS18130 [encoding ATP-binding cassette (ABC) transporters] as well as PP_RS20740 (encoding a hypothetical protein), play pivotal roles in the furfural tolerance and conversion of this bacterium. Finally, strains overexpressing these three striking mutations grew well in highly toxic lignocellulosic hydrolysate, with cell biomass around 9-, 3.6-, and two-fold improvement over the control strain, respectively. To our knowledge, this study first unravels the furan aldehydes tolerance mechanism of industrial workhorse P. putida, which provides a new foundation for engineering strains to enhance furfural tolerance and further facilitate the valorization of lignocellulosic biomass.